2008
DOI: 10.1038/nature07067
|View full text |Cite
|
Sign up to set email alerts
|

Self-destructive cooperation mediated by phenotypic noise

Abstract: In many biological examples of cooperation, individuals that cooperate cannot benefit from the resulting public good. This is especially clear in cases of self-destructive cooperation, where individuals die when helping others. If self-destructive cooperation is genetically encoded, these genes can only be maintained if they are expressed by just a fraction of their carriers, whereas the other fraction benefits from the public good. One mechanism that can mediate this differentiation into two phenotypically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
470
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(484 citation statements)
references
References 28 publications
11
470
2
1
Order By: Relevance
“…Because infection causes the rapid death of the host, an infected individual has little or no opportunity to reproduce until its death, such that the commitment of suicide might simply hasten an individual's inevitable doom. Our findings demonstrate that altruistic host suicide can clearly be delimited from other forms of suicidal behaviours in microbes, such as cell lysis to release toxins [25] or nutrients [26], cell sacrifices to overcome immune systems [27] or to form fruiting body stalks [28,29]. In contrast to the altruistic suicide described in our study, these other behaviours require substantial relatedness among interacting individuals because suicidal cells lose direct fitness benefits.…”
Section: Discussionmentioning
confidence: 52%
“…Because infection causes the rapid death of the host, an infected individual has little or no opportunity to reproduce until its death, such that the commitment of suicide might simply hasten an individual's inevitable doom. Our findings demonstrate that altruistic host suicide can clearly be delimited from other forms of suicidal behaviours in microbes, such as cell lysis to release toxins [25] or nutrients [26], cell sacrifices to overcome immune systems [27] or to form fruiting body stalks [28,29]. In contrast to the altruistic suicide described in our study, these other behaviours require substantial relatedness among interacting individuals because suicidal cells lose direct fitness benefits.…”
Section: Discussionmentioning
confidence: 52%
“…Bistable production of the SPI-1 T3SS in S. Typhimurium has also recently been described (77)(78)(79). The authors observed that nearly 100% of S. Typhimurium cells interacting with intestinal tissues were positive for SPI-1 expression while only 15% of cells in the intestinal lumen were positive (77). The presence of both SPI-1 ϩ and SPI-1 Ϫ cells seems to be important for stabilizing the virulence traits of S. Typhimurium (78).…”
Section: Discussionmentioning
confidence: 81%
“…In Vibrio cholerae, bimodal expression of ToxT results in virulent and nonvirulent cell subpopulations (76). Bistable production of the SPI-1 T3SS in S. Typhimurium has also recently been described (77)(78)(79). The authors observed that nearly 100% of S. Typhimurium cells interacting with intestinal tissues were positive for SPI-1 expression while only 15% of cells in the intestinal lumen were positive (77).…”
Section: Discussionmentioning
confidence: 98%
“…Although traits such as sterility raise important evolutionary questions and can be correlated with whether a major transition has occurred, they are neither necessary nor sufficient for a major transition. Indeed, other examples of complete altruism can be found, which are clearly not major transitions, including bacteria bursting suicidally to release factors that reduce competition (59).…”
Section: Conflict and Maximizing Agentsmentioning
confidence: 99%